Probiotics and competitive exclusion of pathogens in shrimp aquaculture. (24th July 2020) - Knipe, Hazel; Temperton, Ben; Lange, Anke; Bass, David; Tyler, Charles R.
Abstract: Probiotics, live microorganisms that, when administered in adequate amounts, confer a health benefit on the host, offer an alternative to antibiotics and have become popular among shrimp farmers for use in the regulation of pond water quality, promotion of shrimp growth and the prevention of disease. Most shrimp probiotics are selected for testing based on their ability to competitively exclude pathogens through bacterial antagonism assays, although the mechanisms of pathogen exclusion are rarely investigated. In this review, we provide a comprehensive overview of the mechanisms of competitive exclusion (interference and exploitation competition) by species screened and subsequently identified as shrimp probiotics based on their ability to inhibit the growth of pathogenic bacteria in vitro . We show that the current methods used to identify potential probiotics preferentially select for interference‐based competitive mechanisms and may overlook the potential of many species to be considered a probiotic. Furthermore, we show that the efficiency of a probiotic in vivo may be improved by considering the suitability of competitive strategies to shrimp farming conditions. We highlight important limitations and future directions for the screening and identification of probiotics in shrimp aquaculture, to aid in the development of effective and sustainable microbial management strategies.